A Review on Modulation Strategies of Multi Level Inverter - Chinnapettai Ramalingam Balamurugan; S.P. Natarajan; R. Bensraj; B. Shanthi (Institute of Advanced Engineering and Science, 2016)
This review develop different switching methods for Multi Level Inverter (MLI). The switching methods proposed in this paper are to compare various methods and to predict exact switching method for different application based upon its quality of the outputs. The performance of the inverter is analyzed with the parameters like THD (Total Harmonic Injection), VRMS (fundamental), CF (Crest Factor), FF (Form Factor) and DF (Distortion Factor). From the various non PWM (Pulse Width Modulation) and PWM methods the analysis are method to identify the exact PWM strategies for specific applications.